Controlled Polymerization and Polymeric Structures Flow Microreactor Polymerization, Micelles Kinetics, Polypeptide Ordering, Light Emitting Nanostructures - Abe, Akihiro; Lee, Kwang-Sup; Leibler, L.; Kobayashi, Shiro (Advances in Polymer Science,, 2013)
A. Nagaki J. Yoshida Controlled Polymerization in Flow MicroreactorSystems   R. Lund L. Willner D. Richter Kinetics of Block Copolymer Micelles Studied by Small-Angle Scattering Methods   C. Cai J. Lin Z. Zhuang W. Zhu Ordering of Polypeptides in Liquid Crystals,Gels and Micelles   Y.K. Hong D. H. Park S. H. Lee J. Joo Synthesis, Characteristics, and Applications of Intrinsically Light-Emitting Polymer Nanostructures.